Evaluation of sun protecting factor of Calamasi (Citrus x microcarpa) fruits peels formulated into a cream-base sunscreen. - Bibera, Camille C.; Camara, Fletcher Gyb G.; Tajonera Marian U.
The human skin is the largest organ of the body that acts as a barrier for protection against xenobiotic agents and the environment. Chronic exposure to ultraviolet (UV) radiation causes skin problems that could be prevented by the use of physical barriers such as sunglasses, and umbrellas. However, the use of sunscreens is the preferred method of sun protection due to its ease of application and high efficacy of protection. The present study formulated a sunscreen which utilizes calamansi (Citrus *microcarpa) fruit peels based on its reported photoprotective properties. Dried calamansi fruit peels were extracted using 70% ethanol and fractionated with hexane and ethyl acetate. The fraction determined to be with the highest Total Phenolic Content, Total Flavonoid Content, and Sun Protection Factor values will be further used for the formulation of a cream-based sunscreen and will be evaluated for its physicochemical properties, emulsion stability, and Sun Protection Factor through spectrophotometry. Ethyl acetate has been determined to have the highest Total Phenolic and Total Flavonoid Content. Different concentrations (1%, 2%, 3%, 4%, and 6%) of the ethanolic extract of C. microcarpa, and ethyl acetate fraction were added to the formulation. The SPF of formulations containing different concentrations of C. microcarpa were 0.51, 1.83, 3.17. 4.90, 5.76, and 3.11 respectively.